Management control system (MCS) as a support to strategic decision-making: Study in a supermarket chain in the State of Ceará - Alves Júnior, Zacarias Pinheiro; Costas, Mario Helder Lopes; Cabral , Augusto Cézar de Aquino (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This research aims to investigate how the MCS provides support for strategic decision making at companies in the supermarket industry. To this end, a field research was conducted with a qualitative and descriptive approach, through the application of interviews. The research subjects were the associates and the president of a supermarket chain in the State of Ceará. Results evidenced that the MCSs are present in the decision making processes so as to assist associates and the president in strategic planning. However, the network needs to evolve and implement greater MCSs to meet the needs of all associates and the president.